2013
DOI: 10.1007/s00701-013-1931-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of post-operative complications associated with repeat resection and BCNU wafer implantation in recurrent glioblastoma

Abstract: The use of the Stupp protocol as frontline therapy in patients with glioblastoma does not preclude the use of BCNU wafers at the time of progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“… 43 Two articles 44 , 45 used the same experimental data from the study by Westphal et al 6 One study did not present the survival data and we could not contact the author using the email provided in his article. 46 The study focusing on recurrent GBM was also excluded. 47 Finally, seven studies were included in our research.…”
Section: Resultsmentioning
confidence: 99%
“… 43 Two articles 44 , 45 used the same experimental data from the study by Westphal et al 6 One study did not present the survival data and we could not contact the author using the email provided in his article. 46 The study focusing on recurrent GBM was also excluded. 47 Finally, seven studies were included in our research.…”
Section: Resultsmentioning
confidence: 99%
“…One study did not report OS or median survival and was also excluded. 36 All patients had high-grade III or IV glioma. Of the 6 trials, 4 (75%) demonstrated a significant (p ≤ 0.05) percent increase in median survival as compared to control, or non-disruptive treatment (Figure 1).…”
Section: Overall Efficacymentioning
confidence: 98%
“…In the most recently published study on wafer implant therapy, Samis-Zella et al 36 compared the use of implantable wafers for recurrent grade IV GBM with patients with similar glioma who did not get wafer treatment. All patients were given TMZ as well as prophylactic cefazolin and dexamethasone post-surgically.…”
Section: Summary Of Drug Wafer Therapy Studiesmentioning
confidence: 99%
“…Gliadel wafers, a carmustine-imbedded polyanhydride copolymer matrix implant, have perhaps been the most successful localized therapy and are FDA approved for newly diagnosed and recurrent glioblastoma, modestly extending overall survival of both groups 14 . Wafer implantation has drawbacks, however, with increased risk of complications such as surgical site breakdown, infection, cerebrospinal fluid leak, brain edema, hydrocephalus, and cyst formation reported in some studies 15 , though not all 16,17 . Nonetheless, tumor recurrence is common even after carmustine wafer use, with median survival times of 16.4 and 9.7 months for newly diagnosed and recurrent GBM, respectively.…”
mentioning
confidence: 99%